Frequency of Achilles Tenotomy in Patients with Congenital Talipes Equinovarus (CTEV) Treated with Ponseti Technique. (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To determine the frequency of Achilles tenotomy in patients with Congenital Talipes Equinovarus (CTEV) treated with Ponseti serial castings.Methods: This descriptive study was conducted in department of Orthopedic Surgery Khyber Teaching Hospital Peshawar from 12th September 2019 to 12th December 2020. All children of CTEV who were treated with Ponseti serial castings and fulfilled our inclusion criteria were enrolled in this study. Achilles tenotomy was performed at the end of casting in those children who had corrected cavus, varus with head of talus covered and with Pirani Equinus score of 1 or 0.5. The frequency of tenotomy was noted. Important variables of children with tenotomy were stratified and post stratification Chi-square test was applied to calculate P value. P value< 0.05 was considered significant.Results: We treated 86 feet in 69 children with Ponsti serial castings. Majority (75.36%,n=52) of  children had unilateral club foot deformity while 17(24.63%) had bilateral deformity. Male children were 41(59.42%) while 28(40.57%). The mean age at the time of Achilles tenotomy was  10.3+0.28 weeks. The initial Pirani score was 3+0.74 and final Pirani score was 1+0.74. Correction was achieved in 5+0.84 castings. Achilles tenotomy was done in 57 (66.27%) feet to correct the equinus deformity before application of final cast.Conclusion: The frequency of Achilles tenotomy after Ponesti serial casting was high as more than half our children had persistent equinus deformity.